2020
DOI: 10.47197/retos.v0i41.75647
|View full text |Cite
|
Sign up to set email alerts
|

Correlación entre pensamiento táctico y el desarrollo de las habilidades técnicas y físicas de jugadores de fútbol infantil (Correlation between tactical thought and the development of the technical and physical skills of child soccer players)

Abstract: El presente trabajo pretende evidenciar la correlación entre el nivel de pensamiento táctico de los jugadores de fútbol infantil de nivel iniciación en la mejora de las habilidades técnicas y físicas. Metodología: participaron 26 jugadores de fútbol infantil de ocho y nueve años con dos grupos: un grupo con desigualdad numérica y otro con igualdad, ambos con 13 participantes. A los dos grupos se les aplicó una batería de pruebas físicas y técnicas, así como el test del conocimiento táctico ofensivo en el fútbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…The results of this research show that the teaching of technique and tactics has been of significant interest to various researchers [29,33,39,40,47]. In recent years, work has been developed that provides more evidence precisely along these lines, identifying the implications of various factors that affect the development of beginner football [56,57,58].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The results of this research show that the teaching of technique and tactics has been of significant interest to various researchers [29,33,39,40,47]. In recent years, work has been developed that provides more evidence precisely along these lines, identifying the implications of various factors that affect the development of beginner football [56,57,58].…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, in another study developed by Vega-Orozco et al [47] demonstrated that numerical equality or inequality in the development of some exercises can positively impact the development of some technical skills. In situations of numerical inequality, for example, improvements were detected in dribbling and driving the ball in a straight line, findings similar to those reported by Sánchez et al [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khusus pada kemampuan menembak bola ke gawang, jenis kekuatan yang diperlukan adalah integrasi antara kekuatan otot tungkai dan kelentukan otot perut untuk memicu kontraksi otot tungkai untuk menendang bola (Rahmansyah et al, 2018). (Orozco et al, 2020)menyatakan bahwa pengembangan kemampuan fungsional dan sistem tubuh yang baik, dapat menunjang pelaksanaan teknik gerakan secara efektif dan efesien. Berdasarkan teori tersebut, dapat dikemukakan bahwa Kekuatan otot adalah kemampuan untuk pengembangan tenaga maksimum dalam kontraksi yang maksimal untuk mengatasi tahanan atau beban (Draganidis et al, 2013).…”
Section: Hasil Dan Pembahasanunclassified
“…Estas no sólo responden a la situación de la competencia sino a la función del posicionamiento dentro del terreno de juego (Becerra, 2020;Becerra Patiño, 2021;Becerra Patiño, 2022;Moniz Carvalho, Clemente, Praça & da Costa, 2021). A su vez, se busca reconocer que, dentro del fútbol, al ser un deporte colectivo, el desarrollo de la fuerza debe responder a las necesidades del deportista (Vega Orozco, Bernal Reyes, Gavotto Nogales, Sarabia Sainz & Horta Gim, 2021;Becerra Patiño, Prada Clavijo & Sarria Lozano, 2022) buscando favorecer su rendimiento en relación con su posición y no solo generar un desarrollo aislado de los comportamientos y acciones motrices requeridas para su desempeño deportivo (García-Pinillos, Ruiz-Ariza & Latorre-Román, 2015).…”
Section: Introductionunclassified